Republic of the Marshall Islands : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
The Republic of the Marshall Islands (RMI), scattered across an area of nearly 1 million square miles in the Central Pacific, is heavily dependent on external grants. As in past consultations, the current discussions have focused on policies to put public finances on a secure footing and improve growth prospects. Recent economic performance has been lackluster. Exports have been held back mainly by structural problems. The fiscal position has improved in FY2006, but the overall balance has been slightly negative at about 1\2 percent of GDP.